Critical Success Factors of a Jewelry SME from Jalisco to COVID-19: a case study - Rodriguez Aldana, Marcia Lorena; Fong Reynoso, Carlos (Estudios de Administración, 2022)
In Mexico, the jewelry industry of Jalisco contributes with 70% of the national production. The purpose of this document is to analyze the strategic response regarding the key success factors of a SME jewelry factory of Guadalajara, to cope with the COVID-19 arrival, in order to maintain its competitive advantage. Due its nature, the sector is handled with discretion, which makes it difficult to study. For this reason, this investigation shares relevant information. A longitudinal study was carried out from 2019 to 2021 to a factory with 40 years in the sector. It has been found that the SME maintains its competitive advantage through six critical success factors of the industry, which in 2019, in order of importance were price, quality, innovation (technological processes), design (new products), customer service and reputation. It was found that, after coronavirus pandemic, the six factors remain the same, but in a different order. Design has taken the first position and the others are behind. It is concluded that these factors are a whole and all of them are necessary to maintain competitive advantage in the jewelry sector, but their relative importance changes after new market demands.